Spiritualitas Sufistik dan Pencegahan Korupsi: Pendekatan Etika Qur’ani Terhadap Krisis Moral Sosial (Integrasi Etika Ihsan dalam Moralitas Publik) - Ayyasy, Muhammad; Norhidayat, Norhidayat; Mujahid, Ahmad (Sharia Journal and Education Center Publishing, 2026)
This article seeks to explore the relevance of Sufistic spirituality as a basis for moral ethics in preventing social misconduct, particularly through the integration of the value of ihsan within the realm of public morality. Using a descriptive-qualitative approach based on a textual analysis of the Qur’an and classical Sufism literature, this research finds that ihsan defined as spiritual awareness of God’s presence in every action is the core of Sufistic ethics capable of cultivating inner integrity, honesty, and social responsibility. When the value of ihsan is internalized within individuals and social structures, it serves as a preventive mechanism against corrupt behavior and other moral deviations. The Qur’anic ethical approach, rooted in the principles of tazkiyatun nafs (purification of the soul) and muraqabah (self-monitoring), demonstrates that moral reform requires not only a strong legal system but also profound spiritual cultivation. Thus, Sufistic spirituality offers a transcendental ethical paradigm relevant to the formation of a public morality that is clean, just, and oriented toward Divine consciousness.